Um estudo sobre a evolução dos indicadores socioeconômicos no município de Parintins/AM no período de 2000-2010 - Souza, Luana de Souza e (Brasil, 2023)
This study aims to understand the development of the municipality of Parintins/AM, based on social indicators according to the demographic censuses of 2000 and 2010. The social indicators in question were: Human Development Index (MHDI) and its dimensions: health, education and income, and the Gini Index. This period was chosen because it is the most current, because it uses official data from the last two demographic censuses that were collected from the digital collection of the official body: the United Nations Development Program (UNDP). The study presents a theoretical framework that deal with different perspectives of development to enter the discussion about quality of life, allowing a more lucid reading of the data; in addition to exposing the methodology of social indicators. Therefore, analysis of the collected data was performed through the Philcarto Program with the creation of thematic maps. In relation to the comparison is the State of Amazonas, that is, the results of the indexes of municipal indicators are compared with their respective state index. The study showed that the municipality of Parintins had a significant evolution in its MHDI, and especially in its dimensions, including the Education factor that recorded a higher growth than that of the State. Regarding gini index income inequality is still very significant in the municipality, and especially in the State of Amazonas. Although there has been a relative improvement in the Gini de Parintins index, however, it is still not enough to become a more egalitarian municipality.